2017
DOI: 10.14393/bj-v33n5a2017-36547
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among students of a brazilian public university and consequences associated with this consumption

Abstract: ABSTRACT:The present study aimed to evaluate the alcohol consumption profile and behaviors and consequences associated with this consumption among university students. This cross-sectional, observational, and predictive correlational study was conducted with students from a public university in Southeastern Brazil in different course periods (first-year, middle-year and last-year students). Socio-demographic data; prevalence of use of alcohol and other drugs in the previous 12 months and in the previous 30 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…In general, Dos Reis and de Oliveira [ 22 ] found similar results to those in this study and emphasized that Brazilian university students suffering from problematic alcohol use at risk of dependence also tended to use other addictive substances, such as tobacco, cannabis or cocaine. De Oliveira et al [ 56 ] and El Ansari et al [ 57 ] also revealed a significant association between illicit drug use and tobacco use, as well as episodes of binge drinking.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In general, Dos Reis and de Oliveira [ 22 ] found similar results to those in this study and emphasized that Brazilian university students suffering from problematic alcohol use at risk of dependence also tended to use other addictive substances, such as tobacco, cannabis or cocaine. De Oliveira et al [ 56 ] and El Ansari et al [ 57 ] also revealed a significant association between illicit drug use and tobacco use, as well as episodes of binge drinking.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to gender characteristics, there are many other possible determinants of problematic alcohol use such as living away from parents’ home during semesters [ 1 , 17 ], parent attachment [ 18 ], smoking [ 15 ], mental health problems and satisfaction with life [ 19 , 20 ], or age of alcohol consumption onset [ 21 ]. The need to constantly monitor this problem is underlined by the fact that university students who suffer from problematic alcohol use with the risk of dependence are also characterized by the use of other addictive substances, such as tobacco, cannabis or cocaine [ 22 ]. All these factors can contribute to higher levels of alcohol use, which is an undesirable phenomenon in society.…”
Section: Introductionmentioning
confidence: 99%
“…In this research study, the most used drug type during the last 30 days was cannabis, with a prevalence of 15.6%, similar to studies such as the one conducted by Reis et al [ 8 ] in Brazilian students. The rest of the drugs were also used at a similar frequency, except for benzodiazepines, which were used more frequently (11.1%) than in similar populations in other countries (4–7.9%) [ 8 ]. This could be justified by the fact that Spain currently occupies the first place in benzodiazepine use in the world, according to the United Nations [ 63 ].…”
Section: Discussionsupporting
confidence: 83%
“…For example, Tavolacci et al [ 6 ], in a sample of more than 1000 healthcare students, found that one out of four students was an active smoker, used alcohol frequently, or had used psychotropic drugs some time in their lives. In addition, it was found that the use of all these harmful substances tended to cluster at times among university students who used them [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, liquor expands the danger of a wide scope of social damages in the understudy populaces. Studies announced the association between liquor use and missing class, impeded scholarly accomplishment and brutality among college students (Reis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%